2010
DOI: 10.1029/2009jd013238
|View full text |Cite
|
Sign up to set email alerts
|

Sources, compositions, and distributions of water‐soluble organic nitrogen in aerosols over the China Sea

Abstract: [1] Particulate water-soluble organic nitrogen (ON) was measured over the South China Sea, the Yellow Sea and at a coastal site at Qingdao in spring 2005 and 2006 to study its impact on the oceanic ecosystem over the China sea. ON contributed ∼30% of the total water-soluble particulate nitrogen over the South China Sea and ∼20% over the Yellow Sea and in Qingdao. More than 70% of the ON existed in the fine mode particles (<2.1 mm). During dust-storm events, ON in the coarse particles (>2.1 mm) increased leadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
64
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 63 publications
8
64
1
Order By: Relevance
“…Percent contributions of coarse WSON for dust and non-dust events were almost identical, being 58 and 60 %, respectively. A similar enrichment of WSON during dust events has been reported for Erdemli (Mace et al, 2003a), the Yellow Sea (Shi et al, 2010) and Finokalia . In addition, Griffin et al (2007) have demonstrated a significant difference between dust and non-dust events for bacterial-and fungalcolony-forming units at Erdemli, the former being much greater.…”
Section: Influence Of Mineral Dust Episodes On Wson Aerosol Concentrasupporting
confidence: 51%
“…Percent contributions of coarse WSON for dust and non-dust events were almost identical, being 58 and 60 %, respectively. A similar enrichment of WSON during dust events has been reported for Erdemli (Mace et al, 2003a), the Yellow Sea (Shi et al, 2010) and Finokalia . In addition, Griffin et al (2007) have demonstrated a significant difference between dust and non-dust events for bacterial-and fungalcolony-forming units at Erdemli, the former being much greater.…”
Section: Influence Of Mineral Dust Episodes On Wson Aerosol Concentrasupporting
confidence: 51%
“…Organic nitrogen is ubiquitous in the atmosphere and is an important component of wet and dry deposition, including amino acids, urea, organic nitrates, nitro-aromatics, humiclike substances, and others (Cornell et al, 1998;Zhang et al, 2002;Mace et al, 2003;González Benítez et al, 2010;Shi et al, 2010;Violaki and Mihalopoulos, 2011). Two nitrogen-containing organic compounds (carbamide and oxamic acid) were detected here.…”
Section: Organic Nitrogen Speciesmentioning
confidence: 99%
“…Phys., 14, 4185-4199, 2014 www atmosphere, while large fractions of urea were found in the fine mode (< 2.1 µm) in coastal or continental aerosols (Shi et al, 2010). Thus, except for the emissions of urea from primary sources such as agricultural activities, soil dust and the sea surface through bubble-bursting processes (Shi et al, 2010;Violaki and Mihalopoulos, 2011), the secondary production of urea from atmospheric reactions could also be among the major sources. Such a point warrants further studies.…”
Section: Organic Nitrogen Speciesmentioning
confidence: 99%
“…The most identified category of ON in aerosols is reduced nitrogen (N) compounds, which include amino acids (Milne and Zika, 1993), alkyl amines (e.g., Ge et al, 2011a), urea, and N-heterocyclic compounds that originate from biomass burning (Mace et al, 2003), animal husbandry (Schade and Crutzen, 1995), and the ocean surface (Matsumoto and Uematsu, 2005). Shi et al (2010) reported that urea accounted for ∼8% of water-soluble ON on average over the eastern edge of China, where air masses were frequently affected by anthropogenic sources.…”
Section: Introductionmentioning
confidence: 99%